THE USE OF ADVANCED GENOMIC PLATFORMS TO ACCELERATE BREEDING PROGRAMS OF THE INDONESIAN AGENCY FOR AGRICULTURAL RESEARCH AND DEVELOPMENT (A Review) - I Made Tasma (International Journal of Biosciences and Biotechnology, 2015)
The use of advanced genomic platforms such as next generation sequencing (NGS) and highthroughput SNP (HT-SNP) genotyping platform facilitates the use of PGR collection in amore comprehensive manner for a more efficient breeding program. Indonesia is recognizedas the second richest mega-biodiversity in the world. This includes the plant and animal GRof agricultural importance. Few excellent example PGR of Indonesian origin included rice,banana, and sweet potato. The available GR diversity richness must be manipulated forhuman kinds (e.g. breeding purposes) to develop superior crop and animal for food, feed,ornament, and industry. A genomic-based breeding program facilitates the manipulation ofthe wealth GR collection in a more comprehensive, effective, and efficient manner. Thispresentation describes the current status of NGS-based genome sequencing project as well asthe application of HT-SNP array technology in genomic and breeding projects of theIndonesian Agency for Agricultural Research and Development (IAARD). The main cropsand animal under study included soybean, maize, rice, cacao, chili pepper, potato, physic nut,oil palm, and cattle. The sequencing project was done using NGS HiSeq2000 and the SNPchip genotyping study was done using the Illumina iScan. Genome Browser (GB) of thegenomic data was developed containing millions of genomic variations (SNP, Indels, andSSR). The GB is an excellent breeding resource to support breeding program of the crop andanimal under study. The genome browser also contains phenotypic and SNP genotypic dataof specific targeted populations. The SNPs discovered in this study are marker resources forHD SNP chip development. The SNP chips are useful for HT-SNP genotyping projects, GRcharacterization, and gene tagging to identify superior genes and QTLs for characters ofinterest to accelerate national breeding program of the national priority crops and animalunder study.